Dopaminergic agents: back to the basics â A small review - Sharma, Neha Rajkumar; Rane, Meenal; Moin, Shaikh Gulam (Journal of Applied Pharmaceutical Research, 2017)
Parkinsonâs disease is one of the most common neurodegenerative diseases. The motor system is eventually damaged which affects the voluntary movements in a patient. It leads to the death of vital nerve cells in the brain. Women have lesser prevalence due to the hormone called Estrogen which has been playing a significant role in human body. Most of the treatments focus on the balance of Dopamine in the brain which is done with the help of levodopa but the side effects seen in the patients were mild nausea, loss of appetite, heart burn, diarrhea, and many more.  The cause of the disease is still unknown but its occurrence is mainly because of genetic and environmental factors. This review focuses on the combination therapy of levodopa and Carbidopa to treat the symptoms of Parkinsonâs disease.